Manajemen Asuhan Kebidanan Berkelanjutan (Continuity of Care) pada Ibu Hamil, Bersalin, Nifas, dan KB: Studi Kasus di RB dan Klinik Eva Klurak Sidoarjo - Anggy Azaria Putri; Yanik Purwanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Continuity of Care (CoC) is a midwifery care model that provides continuous services from pregnancy, childbirth, postpartum, newborn care, to family planning. This study aimed to describe the implementation of Continuity of Care midwifery services for Mrs. A with a macrosomic infant at Eva Candi Clinic and Maternity Hospital. This study employed a descriptive method with a case study approach. Data were collected through interviews, observations, physical examinations, documentation, and medical records. The results showed that throughout pregnancy, childbirth, postpartum, and newborn care, both the mother and the infant received midwifery care according to the standard of practice. The newborn was delivered in good condition and received essential neonatal care, while the mother experienced a normal postpartum period and received appropriate family planning services. The implementation of Continuity of Care and to supported early detection of complications, improved the quality of midwifery care, and promoted continuous maternal and neonatal health.